Determination of processing conditions for a heat-resistant superalloy used in turbine elements - Kotok, Valerii; Butyrina, Tatyana; Sknar, Yuri; Demchyshyna, Oksana; Liashenko, Anna; Sukha, Irina (Eastern-European Journal of Enterprise Technologies, 2024)
A heat-resistant superalloy from destroyed special equipment was used for further processing to extract valuable metals such as rhenium, nickel, cobalt, tungsten, molybdenum, niobium, tantalum, and others. The need to develop an effective method for the electrochemical dissolution of this superalloy is due to the shortage and high cost of the component metals, especially rhenium. The electrochemical dissolution method is effective for the rapid and complete dissolution of such hard alloys, optimizing the extraction process of valuable components. In the course of the work, the composition of the unknown superalloy was determined, and the possible grade of the alloy was identified as JS32-VI. For the first time, a comparison of the anodic behavior of the heat-resistant superalloy containing rhenium in various electrolyte solutions, including methanesulfonic acid, was carried out. This comparison helped determine which electrolyte is best suited for dissolving the superalloy and extracting valuable metals from it. The results showed that solutions containing chloride ions (NaCl and HCl) are the most effective for the electrochemical dissolution of the superalloy. These results are explained by the fact that chloride ions help remove the passive oxide film from the metal surface. Thus, chloride solutions provide more effective dissolution of the superalloy compared to methanesulfonic acid and sulfuric acid. The key finding of the study is the identification of chloride solutions as the most effective for dissolving the superalloy, which optimizes the process of extracting valuable metals. The application of these methods will contribute to resource conservation and the reduction of production costs, which is important for industries using such materials